„A” i „the” dla uczniów z wyobraźnią – efekty zastosowania gramatyki kognitywnej w szkole - Król-Markefka, Agnieszka (Neofilolog, 2010)
The article presents the results of a quasi-experiment, whose aim was to verify the hypothesis about the advantages of grammatical instruction based on cognitive linguistics principles. Two groups of students took part in a series of lessons, undergoing treatment based either on standard or on cognitive rules concerning the use of English articles. The outcomes of the study demonstrate that although both types of instruction brought positive effects immediately after the treatment, the cognitive group outperformed the traditional group on delayed posttesting.